Impact of different materials on cracking of corrugated fibrecement sheets - Mtsweni, Ntombikayise Beauty (My University, 2014)
The replacement of asbestos fibres with cellulose fibres in producing corrugated fibre reinforced cement sheets by the Hatschek process resulted in edge cracking for stacked sheets. This was due to the hydrophilic nature of cellulose, which increases its tendency for exchanging water with the surroundings. The drying process of corrugated sheets, in a stack, resulted in shrinkage hence edge cracking along the sheet. To reduce the magnitude of drying shrinkage and edge cracking potential, several mitigation strategies were proposed including the surface treatment of cellulose fibres, incorporation of wollastonite microfibres, addition of admixtures and superplasticizers, kaolin inclusion as partial replacement of cement and different exposure conditions. A fundamental understanding in mechanisms behind volume changes and how cracks form was crucial for optimization of the mitigation strategies. This thesis initially used a review approach to understand the mechanisms involved in different types of shrinkage and the role of different mitigation techniques. The ultimate goal was to achieve lower drying shrinkage and cracking risks in corrugated sheets along with reducing its economic impact. As a result, surface treatment of cellulose fibres, based on transforming the hydrophilic nature of cellulose to hydrophobic state, was investigated. Furthermore, inclusion of wollastonite/ kaolin as partial replacement of cement, were evaluated. Also, the potential of adding admixtures/ superplasticizers was explored. Finally, investigation on development of edge cracks in stacked corrugated fibrecement sheets was conducted under different exposure conditions. The results and findings of this research showed no significant improvement in permeability with cellulose surface treatment. Wollastonite microfibres promoted pore discontinuity hence significant reduction in permeability thus lower drying shrinkage. However, the resultant sheets were brittle. By reducing water content with addition of superplasticizers, density was enhanced thus reducing volume change from drying and wetting. Kaolin acted as internal restraint for shrinkage, refining the microstructure at the interfacial transition zone thus increasing density and its pozzolanic reaction enhanced mechanical properties. The inclusion of kaolin in the fibrecement mix in conjunction with controlling exposure conditions managed to eliminate edge cracking.
Keywords: Asbestos cement.; Cement composites.; Fibers.